Print‐Tuning Lateralization and Handedness: an Event‐Related Potential Study in Dyslexic Higher Education Students. (7th December 2015) - van Setten, Ellie R. H.; Martinez‐Ferreiro, Silvia; Maurits, Natasha M.; Maassen, Ben A. M.
Abstract : Despite their ample reading experience, higher education students with dyslexia still show deficits in reading and reading‐related skills. Lateralized print tuning, the early sensitivity to print of the left parietal cortex signalled by the N1 event‐related potential (ERP) component, differs between beginning dyslexic readers and controls. For adults, the findings are mixed. The present study aims to investigate whether print tuning, as indexed by the N1 component, differs between 24 students with dyslexia and 15 non‐dyslexic controls. Because handedness has been linked to lateralization, first, a separate analysis was conducted including only right‐handed participants ( n  = 12 in both groups), like in most previous studies. ERPs were measured during a judgement task, requiring visual, phonological, or semantic judgments. In both groups, the N1 was earlier and stronger in the left than in the right hemisphere. However, when only strongly right‐handed participants were evaluated, the N1 was less left‐lateralized for participants with dyslexia as compared with controls. Participants with dyslexia had longer reaction times during the ERP experiment and performed worse on many reading (‐related) tasks. These findings suggest that abnormal print tuning can still be found among higher education students with dyslexia and that handedness should be regarded in the study of print tuning. Copyright © 2015 John Wiley & Sons, Ltd.